The impact of erythropoietin treatment of anemia on the effectiveness of chemotherapy: analysis of selected parameters and clinical data - Pawlicki, Marek; Kulpa, Jan; Żuchowska, Beata; Rychlik, Urszula; Stasik, Zofia (Contemporary Oncology/Współczesna Onkologia, 2005)
Anemia is a frequent complication of cancer. It may be exclusively a consequence of the presence of malignant disease itself (cancer-related anemia; CRA) or a result of cancer treatment methods, radiotherapy and/or cytotoxic chemotherapy (radio- and chemotherapy-induced anemia). The aim of the presented study was to evaluate effectiveness of anemia treatment with erythropoietin. Pivotal groups of 68 patients were treated with erythropoietin due to cancer-related anemia occurring before or in the course of chemotherapy. The percentage of patients (52.4%) with an observed increase in the hemoglobin level (at least by 2 g/dl) was lower than data published in other studies. The treatment was well tolerated. Only in one case (1.47%) it was necessary to discontinue treatment because of deep vein thrombosis. The effectiveness of erythropoietin treatment seems to depend on the patients\' condition, pretreatment hemoglobin level (<8.5 g/dl) and duration of chemotherapy.